Pro-Inflammatory Effect of Gliadins and Glutenins Extracted from Different Wheat Cultivars on an In Vitro 3D Intestinal Epithelium Model - Truzzi, Francesca (Int J Mol Sci, 2020)
There is a need to assess the relationship between improved rheological properties and the immunogenic potential of wheat proteins. The present study aimed to investigate the in vitro effects of total protein extracts from three modern and two landrace Triticum aestivum commercial flour mixes, with significant differences in gluten strength (GS), on cell lines. Cytotoxicity and innate immune responses induced by wheat proteins were investigated using Caco-2 monocultures, two dimensional (2D) Caco-2/U937 co-cultures, and three dimensional (3D) co-cultures simulating the intestinal mucosa with Caco-2 epithelial cells situated above an extra-cellular matrix containing U937 monocytes and L929 fibroblasts. Modern wheat proteins, with increased GS, significantly reduced Caco-2 cell proliferation and vitality in monoculture and 2D co-cultures than landrace proteins. Modern wheat proteins also augmented Caco-2 monolayer disruption and tight junction protein, occludin, redistribution in 3D co-cultures. Release of interleukin-8 into the cell medium and increased U937 monocyte migration in both 2D and 3D co-cultures were similarly apparent. Immuno-activation of migrating U937 cells was evidenced from cluster of differentiation 14 (CD14) staining and CD11b-related differentiation into macrophages. The modern wheat proteins, with gluten polymorphism relatedness and increased GS, were shown to be more cytotoxic and immunogenic than the landrace wheat proteins.